Peran Teknologi Informasi dalam Melindungi Privasi Pelanggan terhadap Keamanan Data dalam E-Commerce - Dery Shadani; Ahmad Irzi Fahrozi; Fahriza, Hafizh; Hafizh Fahriza; Rizky Alpiansyah; Sulindawaty (GLOBAL SCIENTS PUBLISHER, 2025)
E-commerce has become a very important aspect of daily life in the digital era, increasing efficiency and ease of transactions. But these developments also pose significant risks to the security and privacy of customer data. In the e-commerce ecosystem, information technology (IT) is very important to maintain data security and maintain user privacy. The technologies and procedures used to protect consumer data privacy are discussed in this article. Examples include intrusion detection systems, multifactor authentication, and data encryption. The emergence of e-commerce in Indonesia has raised new prospects and difficulties regarding the confidentiality and security of consumer information. Data security and user privacy are major concerns that can be mitigated by information technology (IT). This article also discusses the difficulties in dealing with the challenges faced in its implementation that supports customer data protection. In addition, this article examines various technologies and strategies to be implemented in e-commerce that are expected to improve data security. A clearer understanding of the role of IT in e-commerce data security will hopefully increase customer confidence and drive long-term growth in the sector.